Community Composition of Beetles (Insecta: Coleoptera) along Elevational Gradients in Phulchowki Hill, Lalitpur, Nepal - Dhakal, Sushma; Budhathoki, Nabin; Subedi, Indra Prasad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Beetles are recognized as important bio-indicators of the ecosystem that can be used to determine species diversity, genetic diversity and ecosystem diversity. We investigated the species composition and diversity of beetles in four seasons along elevational gradients in Phulchowki hill from June 2018 to May 2019. Sampling was done using pitfall traps in five sites located at 1500 m, 1800 m, 2100 m, 2400 m and 2700 m altitude respectively. Overall, we documented 43 morphospecies under 37 genera and 12 families from the study area. Scarabaeidae was the most dominant family whereas Onthophagus sp.2 being the most abundant species in our study. The Shannon-Weiner diversity index, species richness and abundance were highest at 1500 m. Furthermore, diversity and species richness were highest in the spring, whereas peak beetle abundance was observed in summer. Principal component analysis (PCA) was performed to analyze the distribution patterns of the beetle families along the elevational gradients. PCA revealed a strong association of the Carabidae family with 1500 m, 1800 m and 2100 m altitude whereas the Scarabaeidae family were mostly associated with human-influenced areas such as 1500 m and 2700 m altitude. The generalized linear model (GLM) revealed that temperature had a major impact on the overall beetle composition.